The Assessment Of Leadership Style, Competence, Motivation, and Compensation To Employee Performance - Tono Wartono; Bambang Sudaryana (Indonesian Journal of Social Research (IJSR), 2020)
This study aims to analyze the effect of leadership style, motivation and discipline to employee performance. This research was conducted at the Nakhdatul Ulama University Cirebon. The samples in this study were all employees, amounting to as much as 40 respondents. This study is a quantitative research and analysis methods of data using multiple linear regression. The results of this study indicate that the variables of leadership style, motivation and discipline significantly influence employee performance. In partial motivation does not significantly affect the performance of employees while variable leadership style and discipline significantly affect the performance of employees at a significance level of less than 0.05 or 5%.